Recent amendments to the statutory housing agreement - Schedule G: A legal analysis - Md Dahlan, Nuarrual Hilal; Mohd Noor, Fauziah; Shuib, Mohd Sollehudin (2016)
One of the reasons leading to the occurrences of abandoned housing projects in Peninsular Malaysia is the inadequacy of terms and conditions in the statutory housing agreements (Schedules G, H, I and J)(‘the said agreements’) which are capable of protecting the rights and interests of the purchasers. In 2015, there were statutory amendments made to the said agreements. However, so far there is no an attempt looking into the strengths and weaknesses of the terms and conditions in face of abandoned housing projects. This paper aims to analyze these amended terms in Schedule G (landed property) in face of the problems of abandoned housing projects in order to identify any arising issues.The research methodology used is a pure doctrinal legal research methodology.At the end part of this paper, the authors suggest certain improvements to Schedule G, if need be, for the betterment and capable of providing better protection to the victim purchasers in abandoned housing projects in Peninsular Malaysia.